Comparison of the effectiveness of preventive systemic administration of antibiotics with topical use of decamethoxin during clean surgical interventions (Perioperaciina Medicina, 2019)
Introduction. The lack of generally accepted standards of perioperative antimicrobial prophylaxis leads to the inadequate preventive use of antibiotics associated with development of microbial resistance, changes in the natural biota and sensitization of the patient’s body. Prevention of infectious complications after surgery with topical antiseptic is an appropriate alternative to antibiotic prophylaxis. The purpose of this study was to evaluate the efficacy and safety of topical antiseptic prophylaxis of infectious complications with a 0.02 % decamethoxin solution compared to systemic antibiotic prophylaxis with cefuroxime (beta-lactam antibiotics) during clean surgeries.Materials and methods. In the first group of patients (n = 25), the operative field was treated with decametoxin, the abdominal cavity was irrigated through an irrigator during laparoscopic interventions after trocart placement or with a syringe in case of open surgeries (50–150 ml). In the second group (n = 22), cefuroxime was administered at a single dose of 1.5 g 30 to 60 minutes before surgery. Patients underwent inguinal hernia repair (Lichtenstein and laparoscopic transabdominal preperitoneal repair), thyroidectomy, parathyroidectomy, laparoscopic adrenalectomy, cholecystectomy, cystectomy of the spleen and ovaries for uncomplicated cysts.Results. Microbiological analysis of the inoculation material taken from the bottom and walls of the surgical wound before suturing (before the wound was treated with an antiseptic agent in the decamethoxin group) revealed no growth of pathological microbiota at clinically significant levels.Conclusions. The antimicrobial effect of a 0.02 % decamethoxin solution when applied topically during clean surgical interventions is comparable to that of cephalosporin antibiotics. Perioperative antiseptic prophylaxis can reduce the incidence of antibiotic-resistant strains of microorganisms in surgical departments.
Keywords: antimicrobial prophylaxis; antiseptics; decamethoxin; cephalosporins; elective surgery